Targeting the Brain Reservoirs: Toward an HIV Cure - Marban, Céline; Forouzanfar, Faezeh; Ait-Ammar, Amina; Fahmi, Faiza; El Mekdad, Hala; Daouad, Fadoua; Rohr, Olivier; Schwartz, Christian (Frontiers in Immunology, 2016)
One of the top research priorities of the international AIDS society by the action “Towards an HIV Cure” is the purge or the decrease of the pool of all latently infected cells. This strategy is based on reactivation of latently reservoirs (the shock) followed by an intensifying Combination Antiretroviral Therapy (cART) to kill them (the kill). The Central Nervous System (CNS) has potential latently infected cells i.e. perivascular macrophages, microglial cells and astrocytes which will need to be eliminate. However the CNS has several characteristics that may preclude the achievement of a cure. In this review we discuss several limitations to the eradication of brain reservoirs and how we could circumvent these limitations by making it efforts in 4 directions: (i) designing efficient Latency-Reversal Agents for CNS-cell types (ii) improving cART by targeting HIV transcription (iii) improving delivery of HIV drugs in the CNS and in the CNS-cell types (iv) developing therapeutic immunization. As a prerequisite to these efforts we also believe that a better comprehension of molecular mechanisms involved in establishment and persistence of HIV latency in brain reservoirs are essential to design new molecules for strategies aiming to achieve a cure for instance the “shock and kill” strategy.